qPCR analysis of quorum sensing genes of pseudomonas aeruginosa: Primer design and qPCR efficiency - Saiedatul Akmal, Mohamed Sedek; Mohd Azmir, Arifin; Mimi Sakinah, Abdul Munaim (Penerbit Universiti Malaysia Pahang, 2023)
A well-designed and properly validated primer produces a specific and efficient qPCR assay. The primer’s melting temperature, G-C content, its size, as well as the amplicon’s size are the principal considerations while designing the primer for this study and it was in accordance with the MIQE guidelines. Subsequently, the designed primer was evaluated prior to the analysis to verify its efficiency and precision for the relative quantification of the gene transcription analysis. The validity of a qPCR assay is reliant on three elements; the qPCR efficiency (E) and the R2 as well as the slope, that were derived from constructed standard curve. The resulted E for the genes lasI, lasR, rhlI, rhlR and rplS are 92%, 93%, 96%, 92% and 94%, respectively. While the R2 and the slope value for these genes are 0.9991 and -3.523 for the lasI, 0.9991 and -3.501 for the lasR, 0.9989 and -3.434 for the rhlI, 0.9999 and -3.535 for the rhlR, and 0.9935 and -3.487 for the rplS. Melt curve analyses carried out post qPCR assay resulted in amplification of a single product. Resulted E, R2 and slope for all studied genes fell between the acceptable range, validating the use of designed primer for further analysis in the changes in transcription level of quorum sensing genes in treated Pseudomonas aeruginosa.